Product support estimate (PSE) for the beef meat production in Montenegro XE "PSE" - Đurović, Gordana; Bulatović, Branko (Industrija, 2014)
Estimate of support to producers (PSE indicator), according to the OECD methodology, is the annual monetary value of gross transfers from consumers and taxpayers to agricultural producers, resulting from agricultural policy measures. It is very useful indicator for estimation of effectiveness of overall state support to specific agricultural sector or product. This paper presents the first quantification of this indicator for the agricultural manufacturing sector ,in particular beef, given the significant share of livestock in generation of GDP in agriculture (30% and with dairy sector, about 60%; at the same time, beef production is almost 50% of the total value of meat production in Montenegro). The results of this study suggest that the% PSE sector of the beef meat is at a level of 15,63, thanks to higher subsidies and broader funding from other budgetary and credit lines. Comparative analysis shows that this value is greater than in some new EU member states (Romania, Bulgaria), but that is several times lower than the EU average (respective indicator is 50 for beef).